Identification of Aspergillus fumigatus and Related Species by Nested PCR Targeting Ribosomal DNA Internal Transcribed Spacer Regions - Zhao, Jun (American Society for Microbiology, 2001)
Aspergillus fumigatus is the most common species that causes invasive aspergillosis. In order to identify A. fumigatus, partial ribosomal DNA (rDNA) from two to six strains of five different Aspergillus species was sequenced. By comparing sequence data from GenBank, we designed specific primer pairs targeting rDNA internal transcribed spacer (ITS) regions of A. fumigatus. A nested PCR method for identification of other A. fumigatus-related species was established by using the primers. To evaluate the specificities and sensitivities of those primers, 24 isolates of A. fumigatus and variants, 8 isolates of Aspergillus nidulans, 7 isolates of Aspergillus flavus and variants, 8 isolates of Aspergillus terreus, 9 isolates of Aspergillus niger, 1 isolate each of Aspergillus parasiticus, Aspergillus penicilloides, Aspergillus versicolor, Aspergillus wangduanlii, Aspergillus qizutongii, Aspergillus beijingensis, and Exophiala dermatitidis, 4 isolates of Candida, 4 isolates of bacteria, and human DNA were used. The nested PCR method specifically identified the A. fumigatus isolates and closely related species and showed a high degree of sensitivity. Additionally, four A. fumigatus strains that were recently isolated from our clinic were correctly identified by this method. Our results demonstrate that these primers are useful for the identification of A. fumigatus and closely related species in culture and suggest further studies for the identification of Aspergillus fumigatus species in clinical specimens.